Fostering Romanian Civil Protection in the current security context Challenges and Opportunities specific to the Department for Emergency Situations as part of the European Union approach to Civil Protection - DOGEANU, Marius-Daniel; OZUNU, Alexandru (2026)
The analysis focusses on the year 2000, which marks an important turning point with the transfer of civil protection units from the Ministry of National Defence to the Ministry of Interior, as outlined in Emergency Ordinance No. 179 of October 26, 2000. This ordinance also revises the Civil Protection Law No. 106/1996, Government Ordinance No. 47/1994 regarding disaster defence, and Government Emergency Ordinance No. 14/2000 on the establishment of civil protection units for disaster response. The author considers this period as the starting point of moderncivil protection.